PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada Satuan Kerja Perangkat Daerah Kota Dumai) - Raja Yoga Gustika Armel; Azwir Nasir; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to identify the competence of human resources, the impact of government accounting standards, the use of information technology and internal control systems on the quality of government financial reports Dumai. The study was conducted in Dumai SKPD government. Determination of sample criteria based on the premise that the Administrative Unit-Regional Financial Officer Job (KDP-SKPD), the department of finance and treasurer SKPD staff directly involved in the planning, implementation, administration, reporting, accountability and financial oversight of the area. the sample is determined by using purposive sampling and respondent amounted to 87 people. The data used are primary data. Data were collected through questionnaires. Data were analyzed using data analysis techniques to assess the outer SmartPLS models: Convergent Validity, Composite Discriminant Validity and Reliability. The results of this study indicate that the competence of human resources, government accounting standards, the use of information technology and internal control systems to significantly affect the quality of financial reporting. Quality variable Financial Statements (KLK) of 0.89. This shows that 89% of the variable quality of financial reports may be affected by the competence of human resources, utilization of information technology, the implementation of SAP and internal control systems. And the balance of 11% influenced by other factors.Keywords: accounting, control, competencies, technology, and quality